Histone lysine methyltransferases BnaSDG8.A and BnaSDG8.C are involved in the floral transition in Brassica napus. (21st June 2018) - Jiang, Ling; Li, Donghao; Jin, Lu; Ruan, Ying; Shen, Wen‐Hui; Liu, Chunlin
Summary: Although increasing experimental evidence demonstrates that histone methylations play important roles in Arabidopsis plant growth and development, little information is available regarding Brassica napus . In this study, we characterized two genes encoding homologues of the Arabidopsis histone 3 lysine 36 (H3K36) methyltransferase SDG8, namely, BnaSDG8.A and BnaSDG8.C . Although no duplication of SDG8 homologous genes had been previously reported to occur during the evolution of any sequenced species, a domain‐duplication was uncovered in BnaSDG8.C . This duplication led to the identification of a previously unknown NNH domain in the SDG8 homologues, providing a useful reference for future studies and revealing the finer mechanism of SDG8 function. One NNH domain is present in BnaSDG8.A, while two adjacent NNH domains are present in BnaSDG8.C. Reverse transcriptase‐quantitative polymerase chain reaction analysis revealed similar patterns but with varied levels of expression of BnaSDG8.A/C in different plant organs/tissues. To directly investigate their function, BnaSDG8.A / C cDNA was ectopically expressed to complement the Arabidopsis mutant. We observed that the expression of either BnaSDG8.A or BnaSDG8.C could rescue the Arabidopsis sdg8 mutant to the wild‐type phenotype. Using RNAi and CRISPR/Cas9‐mediated gene editing, we obtained BnaSDG8.A / C knockdown and knockout mutants with the early flowering phenotype as compared with the control. Further analysis of two types of the mutants revealed that BnaSDG8.A/C are required for H3K36 m2/3 deposition and prevent the floral transition of B. napus by directly enhancing the H3K36 m2/3 levels at the BnaFLC chromatin loci. This observation on the floral transition by epigenetic modification in B. napus provides useful information for breeding early‐flowering varieties. Significance Statement: Few studies on epigenetics in rapeseed have been reported and here we revealed that no duplication of the SDG8 histone lysine methyltransferase gene had occurred during the evolution of Brassicaceae, but the newfound NNH domain was duplicated within the BnaSDG8.C. The BnaSDG8.A/C directly affect floral transition in Brassica napus primarily by changing the deposition level of H3K36me3 on the BnaFLC2 chromatin, which will provide a useful theoretical guidance for early‐flowering rapeseed breeding.